Groin injuries in soccer: Investigating the effect of age on adductor muscle forces - Dupré, T.; Lysdal, F. G.; Funken, J.; Mortensen, K. R. L.; Müller, R.; Mayer, J.; Krahl, H.; Potthast, W. (Medicine & Science in Sports & Exercise, 2020)
Purpose: The sudden rise in the injury incidence during adolescence is also evident in soccer-related injuries to the groin. Submaximal passing applies high stress on the adductor muscles and pubic symphysis and is therefore likely to be connected to the occurrence of groin injuries. Therefore, the purpose of the study was to compare hip joint kinematics and adductor muscle forces of different adolescent age groups during submaximal soccer passing. Methods: Sixty participants, in four groups, younger than 12, 15, 16. and 23 yr (U12, U15, U16, U23), were analyzed. A Footbonaut, equipped with a 3D motion capture system consisting of 16 cameras, was used to capture kinematic data of short passes. Inverse dynamic analysis was performed to calculate muscle forces of 10 passes of each subject. Results: The U15 group showed reduced angular velocities. A rise in hip adductor muscle forces was evident from the youngest group up to the oldest groups. The largest increase (49%) was found between U12 and U15. Lower-limb mass was identified as the best predictor for the increasing adductor force. Conclusions: The reduced angular velocities of the U15 and the increase in muscle forces between all age groups were attributed to the increasing segment masses and length. This increases the moments of inertia of the leg segments thereby demanding higher forces to accelerate the segments. Most likely, the stress put upon the adductors apophyses increases during adolescence, as tendons are known to adapt slower than muscles, increasing the risk for overuse injuries. Coaches could use lower-limb mass as an indicator for fast increases in the force demand to identify players who would benefit from a reduced training volume.